Infectious bovine keratoconjunctivitis in dairy herds: Presence of haemolytic Moraxella bovis and Moraxella bovoculi - M.V. Zbrun; W. Alvarado; A. Peña; D. Aliprandi; C. Miotti; N. Welschen; D.M. Astesana; J. Cicottello; G. Suarez Archilla; C.M. Camussone; A.I. Molineri; M. Irazoqui; et al. (Research in Veterinary Science, 2026)

Strategic use of enzyme-linked immunosorbent assay as a complementary tool for the diagnosis of bovine tuberculosis - C. Camussone; R.D. Moyano; M.N. Alonso; J. Cicotello; A. Peña; A.I. Molineri; D.M. Astesana; G. Suárez-Archilla; F. Tello D'Elia; D. Aliprandi; N.M. Welschen; M.L. Signorini; et al. (Research in Veterinary Science, 2026)

Cryo-compressed CO2 sorption and diffusion in elastomers for the CO2 transport chain: Examples of FKM, EPDM and HNBR - E. Ghiara; G. Lazzari; V. Signorini; L. Ansaloni; B. Alcock; M. Minelli (Chemical Engineering Journal, 2025)

Analyzing soil enzymes to assess soil quality parameters in long-term copper accumulation through a machine learning approach - G. Genova; L. Borruso; M. Signorini; M. Mitterer; G. Niedrist; S. Cesco; B. Felderer; L. Cavani; T. Mimmo (Applied Soil Ecology, 2024)

Fetal heart rate spectral analysis in raw signals and PRSA-derived curve: normal and pathological fetuses discrimination - Giulio Steyde; Edoardo Spairani; Giovanni Magenes; Maria G. Signorini (Medical & Biological Engineering & Computing, 2024)
Cardiotocography (CTG) is the most common technique for electronic fetal monitoring and consists of the simultaneous recording of fetal heart rate (FHR) and uterine contractions. In analogy with the adult case, spectral analysis of the FHR signal can be used to assess the functionality of the autonomic nervous system. To do so, several methods can be employed, each of which has its strengths and limitations. This paper aims at performing a methodological investigation on FHR spectral analysis adopting 4 different spectrum estimators and a novel PRSA-based spectral method. The performances have been evaluated in terms of the ability of the various methods to detect changes in the FHR in two common pregnancy complications: intrauterine growth restriction (IUGR) and gestational diabetes. A balanced dataset containing 2178 recordings distributed between the 32nd and 38th week of gestation was used. The results show that the spectral method derived from the PRSA better differentiates high-risk pregnancies vs. controls compared to the others. Specifically, it more robustly detects an increase in power percentage within the movement frequency band and a decrease in high frequency between pregnancies at high risk in comparison to those at low risk. Graphical abstract

Quantitative microbial spoilage risk assessment caused by fungi in sports drinks through multilevel modelling - Félix G. Ramos Guerrero; Marcelo Signorini; Alberto Garre; Anderson S. Sant'Ana; Juan C. Ramos Gorbeña; Marcial I. Silva Jaimes (Food Microbiology, 2023)

Characterization of lesions of nutritional congenital goitre in cattle - Luis A. Colque-Caro; Francisco Acuña; Laura S. Aguirre; Agustín Avellaneda-Cáceres; Claudio G. Barbeito; Marcelo Signorini; Dadin P. Moore; Juan F. Micheloud (Journal of Comparative Pathology, 2023)

Multi-parametric cardiorespiratory analysis in late-preterm, early-term, and full-term infants at birth - Maristella Lucchini; Nina Burtchen; William P. Fifer; Maria G. Signorini (Medical & Biological Engineering & Computing, 2019)

Complexity analysis of the fetal heart rate variability: early identification of severe intrauterine growth-restricted fetuses - Manuela Ferrario; Maria G. Signorini; Giovanni Magenes (Medical & Biological Engineering & Computing, 2009)

Prevalence and incidence of antibodies to Borrelia burgdorferi and to tick-borne encephalitis virus in agricultural and forestry workers from Tuscany, Italy - P. Tomao; L. Ciceroni; M. C. D’Ovidio; M. Rosa; N. Vonesch; S. Iavicoli; S. Signorini; S. Ciarrocchi; M. G. Ciufolini; C. Fiorentini; B. Papaleo (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Veterinary Case History: Forensic and Medical Legal Aspects - G. Signorini; G. Biagi; E. Luchetti; G. Cardini; R. Bernocchi (Veterinary Research Communications, 2004)